Ecology and geography of transmission of two bat-borne rabies lineages in Chile. - Luis E Escobar (Public Library of Science (PLoS), 2013)
Rabies was known to humans as a disease thousands of years ago. In America, insectivorous bats are natural reservoirs of rabies virus. The bat species Tadarida brasiliensis and Lasiurus cinereus, with their respective, host-specific rabies virus variants AgV4 and AgV6, are the principal rabies reservoirs in Chile. However, little is known about the roles of bat species in the ecology and geographic distribution of the virus. This contribution aims to address a series of questions regarding the ecology of rabies transmission in Chile. Analyzing records from 1985-2011 at the Instituto de Salud Pública de Chile (ISP) and using ecological niche modeling, we address these questions to help in understanding rabies-bat ecological dynamics in South America. We found ecological niche identity between both hosts and both viral variants, indicating that niches of all actors in the system are undifferentiated, although the viruses do not necessarily occupy the full geographic distributions of their hosts. Bat species and rabies viruses share similar niches, and our models had significant predictive power even across unsampled regions; results thus suggest that outbreaks may occur under consistent, stable, and predictable circumstances.